Ilmu Pengetahuan Sebagai Pilar Peradaban - Arisanti, Kustiana (Humanistika : Jurnal Keislaman, 2018)
AbstractÂ Islam is a rational religion and a scientific religion. As a rational and scientific religion the mark always lays the foundations that conform to scientific standards and can be proved by reason in various shariah and other rule provisions. Rasulullah Saw. as a carrier, spreader and proselytizer of Islamic Sharia laid a solid foundation as a rational religion. This is seen in his words "religion is the intellect and imperfect of ones religion without using reason".As a rational religion, Islam declares its people to always base their activities with knowledge. Without the knowledge of worship is rejected. So Islam commands his people to read, study, research science, both in the perspective of Islamic religious sciences and other general sciences. They are very urgent and significant for the survival of Muslims and Muslims themselves. Science is the key to success (key of success) of all activities. Besides, science is also the standard of civilization left behind and passed on to the next generation.Â Keywords: rational religion, scientific religion.